2021
DOI: 10.3390/architecture1020008
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Using Plants in Indoor Environments: Exploring Common Research Gaps

Abstract: The introduction of green plants in indoor spaces has raised a great amount of interest motivated by plants’ supposed capacity to improve the quality of indoor built environments. Subsequent studies have covered a broad range of topics, testing plants in indoor environments for their climate-mitigating effects, acoustic benefits, potential energy savings and the enhancement of the indoor microbial communities. Despite the diversity of focus in these studies, no major breakthroughs have been made involving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The research into the effect of plants usually focuses on the effects of single plants of different species in different conditions. Attention should further be placed on species that can cohabitate together, thus compensating each other’s needs and recreating the basic forms of symbiosis [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research into the effect of plants usually focuses on the effects of single plants of different species in different conditions. Attention should further be placed on species that can cohabitate together, thus compensating each other’s needs and recreating the basic forms of symbiosis [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various scholars have suggested that placing plants around people brings multiple benefits (Persiani, 2021;Bak Yao, 2020). Plants help increase concentration and strengthen memory, create happy emotions within occupants, provide healing effects, boost human performance, and improve mental health by reducing stress through therapeutic efficacy.…”
Section: Accessibility To Natural Elementsmentioning
confidence: 99%
“…Individuating large-scale effects dependent on plant emissions is demanding, although it could be estimated via extended monitoring and real-time sampling of the urban and wild environment (for instance PTR-MS), or via prediction models (Guenther et al, 2006), which could show particular trend distributions of biogenic fluxes (Chuang et al, 2011;Seco et al, 2015;Drewer et al, 2018;Coggon et al, 2021). In the city area the impact of BVOC emissions regarding green-integrated infrastructures was already theorized (Niinemets and Peñuelas, 2008;Tiwari et al, 2019;Persiani, 2021), but currently research targeting the assessment of BVOC levels in urban environments is limited (Yang et al, 2009;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%